Faktor – Faktor Yang Mempengaruhi Profitabilitas Perbankan Di Indonesia - Prayoga, Agung Kusuma; Alfiyanti, Wulan; Muchtar, Susy (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2025)
This study explores the impact of entrepreneurship training on the empowerment of rural communities in Margo Mulyo Village, Rantau Pulung Sub-District, East Kutai Regency. The objective of the programme was to enhance community capabilities in managing and developing local economic potential through the application of entrepreneurial knowledge and skills. The training covered topics such as business planning, marketing strategies, digital branding, and basic financial literacy. A participatory approach was used, involving local residents in workshops, simulations, and direct mentoring. The results indicate that participants demonstrated increased confidence, improved understanding of business concepts, and stronger motivation to start or improve small-scale enterprises. Several participantsinitiated product development and established microbusiness ventures after completing the training. Furthermore, the programme fostered collaboration among community members, creating a support system that contributes to sustainable development. Challenges encountered included limited digital access and initial resistance to change, which were mitigated through adaptive facilitation and community engagement. Overall, the findings suggest that entrepreneurship training can be an effective instrument for empowering rural communities, encouraging self-sufficiency, and promoting local economic growth. The study recommends the integration of similar training modules in rural development initiatives, particularly in areas with high economic vulnerability. Future programmes should also consider follow-up assistance and access to markets to maximise long-term outcomes.